Предмет: Алгебра,
автор: MarySestra
Решите уравнение методом замены переменной.
x²-x-1 6x
____ - ______ = 5
x x²-x-1
Ответы
Автор ответа:
0
(x²-x-1)/x-6x/(x²-x-1)=5
Пусть (x²-x-1)/x=t ⇒
t-6/t=5
t²-5t-6=0 D=49
t₁=-1 ⇒ (x²-x-1)/x=-1 x²-x-1=-x x²-1=0 x²=1 x₁=1 x₂=-1
t₂=6 ⇒ (x²-x-1)/x=6 x²-x-1=6x x²-7x-1=0 D=53 x₃,₄=(7+/-√53)/2
Пусть (x²-x-1)/x=t ⇒
t-6/t=5
t²-5t-6=0 D=49
t₁=-1 ⇒ (x²-x-1)/x=-1 x²-x-1=-x x²-1=0 x²=1 x₁=1 x₂=-1
t₂=6 ⇒ (x²-x-1)/x=6 x²-x-1=6x x²-7x-1=0 D=53 x₃,₄=(7+/-√53)/2
Похожие вопросы
Предмет: Физика,
автор: Skrebatuna
Предмет: Физика,
автор: Skrebatuna
Предмет: Литература,
автор: rainspacebow84
Предмет: Математика,
автор: ekaterinaleskina
Предмет: Геометрия,
автор: botan11m